Clustering of meteorological and qualitative variables of graywater in a solar reactor - Cavalcante, Fernanda Lima; Bezerra, Joel Medeiros; Queluz, João Gabriel Thomaz [UNESP]; Sánchez-Román, Rodrigo Máximo [UNESP]; Dombroski, Solange Aparecida Goularte; Batista, Rafael Oliveira (Centro Universitario de Maringa, 2021)
Inadequate environmental sanitation contributes to the pollution of water sources, as well as the emergence of cases of water-borne diseases. However, solar radiation is a low-cost, easy-to-operate and effective alternative for greywater disinfection. The objective of this study was to identify the groupings of meteorological and qualitative variables of samples of graywater treated in a solar reactor in the semi-arid region of Rio Grande do Norte. For this, a greywater treatment plant consisting of a septic tank, anaerobic filter and solar reactor was used. Tests were performed from July to December 2015, monthly. In the solar reactor, 0.1 m greywater sheets were kept, which were exposed to solar radiation from 8 am to 4 pm, and aliquots were collected every two hours. The collected samples were submitted to pH, dissolved oxygen, temperature, electrical conductivity, total suspended solids, turbidity, total coliforms, E.coli, and helminth eggs analyses. The following variables were also monitored: air temperature and global solar radiation. The data obtained were submitted to hierarchical clustering analysis that resulted in the formation of four groups, demonstrating that the clustering occurred as a function of seasonality, and the time of sun exposure to which the graywater samples were submitted. Solar disinfection is a technically and economically viable alternative that allows a significant reduction in pathogens, enabling the agricultural use of graywater.
Agrupamento de variáveis meteorológicas e qualitativas de água cinza em reator solar*
Keywords: Bacteria; Decay; Reactor; Wastewater